Arc routing under uncertainty: Introduction and literature review. (November 2021) - De Maio, Annarita; Laganà, Demetrio; Musmanno, Roberto; Vocaturo, Francesca
Highlights: We review the scientific literature on arc routing problems under uncertainty. We prevalently focus on stochastic programs and robust optimization models. Basic concepts and methodological aspects in uncertain domains are illustrated. We give an overview of the different applications within the area of interest. We discuss future research directions about uncertain arc routing problems. Abstract: This article provides a summary of the scientific literature on arc routing problems under uncertainty. Uncertainty is involved in any problem-solving situation where information is incomplete, fragmentary, not readily available, not fully exploitable, or deficient in some other way. Here, we deal with different types of uncertainty and also refer to vagueness that arises in fuzzy environments. The article prevalently focuses on problems represented as stochastic programs or robust optimization models for which the basic concepts are illustrated. In addition, other paradigms are discussed, like the ones dealing with uncertain aspects in dynamic domains. The main solution methods for these uncertain problems are presented. The article also provides an overview of the different applications within the area of interest.